A Review on Acute Respiratory Distress Syndrome in Animal Models - Panda , Subham Kumar; Sharma, V. G. S.; Ray, B. (Innovations in Biological Science Vol. 5, 2024)
The present study provides the various methods for insulting ARDS in animal model, along with advantage and disadvantage of each method. Acute Respiratory Distress Syndrome (ARDS) is an acute inflammatory lung injury. There is an immune-cell-mediated decline of the alveolar epithelial-interstitial-endothelial complex walls in the exudative phase, permitting plasma, plasma proteins, and cellular content into successively flood the interstitium and airspace. ARDS occurs when there is disruption in the alveolar-capillary barrier followed by the deposition of protein rich fluid inside the alveoli of the lungs. Less oxygen reaches the bloodstream as a result of this protein-rich fluid, which prevents the lungs from filling with enough air. As a result, the organs lose some of the oxygen necessary for normal operation. Aspiration of stomach contents, pneumonia, sepsis, and severe trauma are among the several clinical conditions linked to the onset of ARDS. The various clinical disorders that are associated with the development of ARDS include sepsis, pneumonia, aspiration of gastric contents, and major trauma. Human ARDS is not caused by any single event and hence here is no such existing animal model that would completely mimic Human ARDS.